LOCATION AND AVERAGE CLASS SIZE AS FACTORS IN ACHIEVEMENT IN JSC MATHEMATICS EXAMINATION - Okoye, Romy O.; Aloysius, Anyichie C. (Sokoto Educational Review, 2020)
The purpose of this study was to find out if there was an association between achievement in JSC Mathematics Examination and class size on one hand and the level of noise around the school on the other hand. The Mathematics results o f a sample of 7,276 students who took JSCE in 2003/2004, 2004/2005 and 2005/2006 in Onitsha North Local Government Area of Anambra State were obtained after the schools in that Local Government Area had been stratified according to level of noise around the school and then according to average class size. The result of the study established a negative association between academic achievement and average class size on one hand, and level of noise on the other. From the results one concludes that a student is more likely to perform better in JSC Mathematics Examination, if he is in a school with small average class size, or one in a less noisy area, than if he is in a school with large average class size or one in a highly noisy area.